Adapting creative problem solving to an organizational context: a study of its effectiveness with a student population - Cardoso de Sousa, Fernando (2015)
Owing to company time restrictions and concentration on project development, we began to reduce the duration of creative problem solving (CPS) sessions, and to give more emphasis to the action planning stage. Several changes in our CPS protocol, as well as in its duration, begged the question as to whether these changes were jeopardizing efficacy. To examine this question, six groups of ten university students, working under two different CPS protocols (a five-step method and a four-step method), and three control groups (using no CPS method), were given the same objective and similar conditions. This exploratory experiment compared group performance by change in team commitment, divergent thinking preferences, productivity and the participants' evaluation of the different methods. Results show that the CPS methods were both effective in changing participants' perspectives regarding divergent thinking and team commitment. In the control groups, however, there were no changes as a consequence of the sessions. Results also suggest that the same problem-solving effectiveness can be attained in a shorter time than that traditionally used, and without prior training in CPS. These findings open the door to developing new problem-solving techniques and team work processes, and to more efficient organizational creativity and innovation methodologies.